The summer we got free - McKenzie, Mia (Oakland, CA : BGD Press, 2012)
"At one time a wild young girl and a brilliant artist, Ava Delaney changes dramatically after a violent event that rocks her entire family. Once loved and respected in their community and in their church, the Delaneys are ostracized by their neighbors, led by their church leader, and a seventeen year feud ensues. Ava and her family are displaced from the community even as they continue to live within it, trapped inside their creaky, shadowy old house. When a mysterious woman arrives unexpectedly for a visit, her presence stirs up the past and ghosts and other restless things begin to emerge. And something is reignited in Ava: the indifferent woman she has become begins to give way to the wild girl, and the passionate artist, she used to be. But not without a struggle that threatens her life."--Publisher's description
Keywords: Homosexuality -- Fiction; Lesbianism -- Fiction; Young women -- Fiction; Lesbian fiction; Fiction